2016
DOI: 10.1038/nn.4394
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensing is critical for axon growth in the developing brain

Abstract: During nervous system development, neurons extend axons along well-defined pathways. The current understanding of axon pathfinding is based mainly on chemical signalling. However, growing neurons interact not only chemically but also mechanically with their environment. Here we identify mechanical signals as important regulators of axon pathfinding. In vitro, substrate stiffness determined growth patterns of Xenopus retinal ganglion cell (RGC) axons. In vivo atomic force microscopy revealed striking stiffness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
630
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 536 publications
(658 citation statements)
references
References 58 publications
25
630
1
2
Order By: Relevance
“…A recent report noted a pattern of stiffness gradients in the embryonic brain, as measured using in situ atomic force microscopy (AFM) (Koser et al, 2016), and the SVZ specifically is known to stiffen gradually over the course of embryonic development (Iwashita et al, 2014), although the bulk elastic modulus of the brain does not appreciably change during development or postnatally (Majkut et al, 2013). Directly altering brain stiffness or blocking mechanotransduction during development results in aberrant axonal growth and migration (Koser et al, 2016), also implicating mechanical signals as regulators of this process. Defining the mechanical microenvironment of stem cell niches and understanding their contribution to cell behavior will enhance our ability to generate in vitro culture conditions that more faithfully mimic physiological environments.…”
Section: Ecm In the Developing Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report noted a pattern of stiffness gradients in the embryonic brain, as measured using in situ atomic force microscopy (AFM) (Koser et al, 2016), and the SVZ specifically is known to stiffen gradually over the course of embryonic development (Iwashita et al, 2014), although the bulk elastic modulus of the brain does not appreciably change during development or postnatally (Majkut et al, 2013). Directly altering brain stiffness or blocking mechanotransduction during development results in aberrant axonal growth and migration (Koser et al, 2016), also implicating mechanical signals as regulators of this process. Defining the mechanical microenvironment of stem cell niches and understanding their contribution to cell behavior will enhance our ability to generate in vitro culture conditions that more faithfully mimic physiological environments.…”
Section: Ecm In the Developing Brainmentioning
confidence: 99%
“…Differentiation into more specialized neuronal subtypes can also be optimized through mechanical manipulations; for example, motor neuron differentiation of human pluripotent stem cells is most efficient on soft versus stiff micropost arrays, and mediated through a YAPdependent mechanism (Sun et al, 2014). Functional cellular properties might also rely on mechanical signals; for example, the growth of retinal ganglion axons has recently been found to rely on the ability of cells to sense local tissue stiffness through mechanosensitive ion channels (Koser et al, 2016). These studies indicate that the stiffness on which individual neuronal subtypes are grown could be important to their functionality, so measuring and mimicking this feature of the in vivo environment can be used to direct stem cell fate.…”
Section: Neuronal Cell Mechanical Properties and Differentiationmentioning
confidence: 99%
“…The intrinsic mechanical properties of the body determine neuronal differentiation, dynamics, behavior, and organization (Hynes, 2009;Janmey and Miller, 2011;Koser et al, 2016). The importance of substrate mechanics as a cue is evident during differentiation of stem cells in environments of controlled stiffness.…”
Section: Manipulation Of Substrate Stiffnessmentioning
confidence: 99%
“…During embryonic development, many biological processes are regulated by tissue mechanics in vivo, including cell migration 1 , neuronal growth 2 , and large-scale tissue remodelling 3,4 . Recent measurements at specific time points suggested that tissue mechanics change during developmental 2,5,6 and pathological 7,8 processes, which might significantly impact cell function.…”
mentioning
confidence: 99%